A functional circadian clock is required for proper insulin secretion by human pancreatic islet cells. Issue 4 (22nd January 2016) - Saini, C.; Petrenko, V.; Pulimeno, P.; Giovannoni, L.; Berney, T.; Hebrok, M.; Howald, C.; Dermitzakis, E. T.; Dibner, C.
Abstract : Aim: To determine the impact of a functional human islet clock on insulin secretion and gene transcription. Methods: Efficient circadian clock disruption was achieved in human pancreatic islet cells by small interfering RNA‐mediated knockdown of CLOCK . Human islet secretory function was assessed in the presence or absence of a functional circadian clock by stimulated insulin secretion assays, and by continuous around‐the‐clock monitoring of basal insulin secretion. Large‐scale transcription analysis was accomplished by RNA sequencing, followed by quantitative RT‐PCR analysis of selected targets. Results: Circadian clock disruption resulted in a significant decrease in both acute and chronic glucose‐stimulated insulin secretion. Moreover, basal insulin secretion by human islet cells synchronized in vitro exhibited a circadian pattern, which was perturbed upon clock disruption. RNA sequencing analysis suggested alterations in 352 transcript levels upon circadian clock disruption. Among them, key regulators of the insulin secretion pathway ( GNAQ, ATP1A1, ATP5G2, KCNJ11 ) and transcripts required for granule maturation and release ( VAMP3, STX6, SLC30A8 ) were affected. Conclusions: Using our newly developed experimental approach for efficient clock disruption in human pancreatic islet cells, we show for the first time that a functional β‐cell clock is required for proper basal and stimulated insulin secretion. Moreover, clock disruption has a profound impact on the human islet transcriptome, in particular, on the genes involved in insulin secretion.